Estilos de afrontamiento en mujeres diagnosticadas con Virus de Papiloma Humano (VPH) nacidas en el Charco Nariño (2024)
This study focuses on describing coping styles used by women born in El Charco, Nariño, facing the diagnosis of human papillomavirus (HPV). Employing a qualitative methodology and a descriptive approach, socio-demographic characteristics of five women diagnosed with HPV were characterized, examining both problem-focused and emotion-focused coping styles. Through semi-structured interviews and questionnaires, detailed information on participants' experiences and coping strategies was gathered.